Co-occurrence of VHL and SDHA Pathogenic Variants: A Case Report - Tung, Moon Ley; Chandra, Bharatendu; Dillahunt, Kyle; Gosse, Matthew D.; Sato, T. Shawn; Sidhu, Alpa (Frontiers in Oncology, 2022)
Von Hippel Lindau syndrome presents with cerebellar and spinal hemangioblastomas, renal cell cancer, neuroendocrine pancreatic tumor, and pheochromocytoma. Pathogenic variants in the SDHA gene are associated with paraganglioma and pheochromocytoma. Here we report co-occurrence of both VHL and SDHA pathogenic variants in a patient who presented with pancreatic neuroendocrine tumor. As these genes converge on the pseudo-hypoxia signaling pathway, further studies are warranted to determine the significance of co-occurrence of these variants in relation to tumor penetrance, disease severity, treatment response and clinical outcomes in this selected group of patients.